2019
DOI: 10.7717/peerj.6653
|View full text |Cite
|
Sign up to set email alerts
|

Photo-hydrogen and lipid production from lactate, acetate, butyrate, and sugar manufacturing wastewater with an alternative nitrogen source byRhodobactersp.KKU-PS1

Abstract: Photo-hydrogen and lipid production from individual synthetic volatile fatty acids (VFAs) and sugar manufacturing wastewater (SMW) by Rhodobacter sp. KKU-PS1 with sodium glutamate or Aji-L (i.e., waste from the process of crystallizing monosodium glutamate) as a nitrogen source was investigated. Using individual synthetic VFAs, the maximum hydrogen production was achieved with Aji-L as a nitrogen source rather than sodium glutamate. The maximum hydrogen production was 1,727, 754 and 1,353 mL H2/L, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…They concluded that the substrate preference of the ASMC is in the order of glucose > acetic acid > mannitol > lactic acid. A similar order (acetic > butyric > lactic acid) was obtained by Assawamongkholsiri et al 50 when the SCCAs were individually used as carbon source for lipid production in Rhodobacter sp. KKU-PS1.…”
Section: Monomerssupporting
confidence: 76%
“…They concluded that the substrate preference of the ASMC is in the order of glucose > acetic acid > mannitol > lactic acid. A similar order (acetic > butyric > lactic acid) was obtained by Assawamongkholsiri et al 50 when the SCCAs were individually used as carbon source for lipid production in Rhodobacter sp. KKU-PS1.…”
Section: Monomerssupporting
confidence: 76%
“…As can be seen, the range of microorganisms for the production of lipids is diverse, including bacteria ( Rhodobacter sp. KKU-PS1), yeasts and fungi ( Y. lipolytica and Cryptococcus curvatus ), and even microalgae ( Auraniochytrium limacinum SR21) [ 97 , 98 , 99 , 100 ].…”
Section: Products From Acetatementioning
confidence: 99%